Systematic Analysis of tRNA-Derived Small RNAs Discloses New Therapeutic Targets of Caloric Restriction in Myocardial Ischemic Rats - Liu, Wenjing; Liu, Yang; Pan, Zhaohai; Zhang, Xin; Qin, Yao; Chen, Xiaojie; Li, Minjing; Chen, Xiaoyu; Zheng, Qiusheng; Liu, Xiaona; Li, Defang (Frontiers in Cell and Developmental Biology, 2020)
Caloric restriction (CR) is a novel dietary therapy that has a protective effect on myocardial ischemia. However, the mechanisms underlying the therapeutic effect of CR remain unclear. Transfer RNA (tRNA)-derived small RNAs (tsRNAs) are a novel type of short non-coding RNAs that have potential regulatory functions in various physiological and pathological processes. In this study, we explored new therapeutic targets of CR through tsRNA sequencing. Rats were randomly divided into three groups: a normal control group (Norm group), isoproterenol (ISO)-induced myocardial ischemic group (MI group), and CR-pretreatment plus ISO-induced myocardial ischemic group (CR+MI group). Triphenyl tetrazolium chloride (TTC) staining, terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining, creatine kinase (CK) assays, and serum lactic acid dehydrogenase (LDH) levels were used to measure the degree of myocardial ischemic injury. These indicators of myocardial ischemia were significantly improved in the CR+MI group compared with those in the MI group. In the ischemic myocardial tissue of the MI group, a total of 708 precisely matched tsRNAs were identified, and 302 tsRNAs (fold change > 1.5, P < 0.05) were significantly changed when compared with those in the Norm group. Furthermore, 55 tsRNAs were significantly regulated by CR pretreatment, among which five tsRNAs (tiRNA-His-GTG-004, tRF-Gly-TCC-018, tRF-Cys-GCA-022, tRF-Lys-CTT-026, tRF-Met-CAT-008) were randomly selected and verified by quantitative real-time PCR. In addition, predictions of target genes and bioinformatic analysis indicated that these tsRNAs may play a therapeutic role through the regulation of macromolecular metabolism. In conclusion, our findings reveal that tsRNAs are potential therapeutic targets for CR pre-pretreatment to improve myocardial ischemic injury. This study provides new ideas for future research on elucidating the mechanisms of CR pretreatment in ameliorating myocardial ischemic injury.